Factors Associated with Distant Metastasis from Cutaneous Melanoma: A Study at Maharaj Nakorn Chiang Mai Hospital - Chaichan, Wasuchon; Mahanupab, Pongsak; Chuamanochan, Mati; Tovanabutra, Napatra; Chiewchanvit, Siri (Biomedical Sciences and Clinical Medicine, 2022)
OBJECTIVE Cutaneous melanoma is an aggressive tumor associated with high mortality, particularly in the advanced stages. The objective of this study is to identify risk factors for distant metastasis in melanoma patients. METHODS This retrospective analytical study included all patients diagnosed with cutaneous melanoma and treated at Maharaj Nakorn Chiang Mai Hospital between January 2002 and July 2019. RESULTS One hundred and forty patients were enrolled in the study. Distant metastasis was found in 45% of the patients (n = 63) and the most common site was the lung (27.9%, n = 39). Multivariable analysis detected two significant prognostic factors for distant metastasis: Breslow thickness 2-4 mm and > 4 mm (p = 0.048 and 0.045, respectively) and nodal metastasis (p < 0.0001). CONCLUSIONS Breslow thickness > 2 mm and nodal metastasis are associated with distant metastasis and the lung is the most common site of distant metastasis. The patients found to be at risk should be aggressively investigated for distant metastasis.